Ultrasound-Guided Percutaneous Lower Brachial Artery Access Closure Using a Suture-Mediated Closure Device: A Single-Center Experience in 23 Cases - Bellam Premnath, Krishna Prasad; Shariq, Mohd; Hegab, Shady; Saleh, Ahmed; Elsakhawy, Mahmoud (Journal of Clinical Interventional Radiology ISVIR, 2025)
The aim of the study was to evaluate the efficacy and safety of ultrasound-guided suture-based ProGlide/ProStyle closure device for brachial artery access closure after interventional radiology procedures.A modified technique of ProGlide/ProStyle percutaneous suture deployment with ultrasound guidance was used for brachial artery access closure (23 procedures in 21 patients) between June 2019 and June 2024. The only exclusion criterion was a brachial artery diameter of less than 4 mm. The primary outcome measure was the incidence of reintervention from device failure and the secondary outcome measure was the incidence of brachial access site complications. Ultrasound appearances of the brachial artery immediately and 1 day after access site closure were documented, and clinically followed up 60 days after access site closure.There was successful closure in all arteries, and none required access site reintervention. There were no major vascular complications in any of our cases. There were no major access site–related complications. Ten of 23 (43.5%) cases showed vasospasm cranial to the closure site on ultrasound, which disappeared on the follow-up ultrasound performed the day after access site closure.This novel ultrasound-guided ProGlide/ProStyle deployment for brachial vascular closure is efficacious and safe.
Keywords: brachial access; Perclose ProGlide/ProStyle; suture-mediated closure device